THE MOTIVATION OF UNIVERSITY STUDENTS AS AN ACTUAL ISSUE IN PSYCHOLOGY AND PEDAGOGY - Agazade, Nigar; Sudzhaeva, Narmin (Publishing house «UKRLOGOS Group», 2024)
Pedagogy and psychology coexist in the field of education. Each of these subjects makes a significant contribution. Pedagogy is a branch of knowledge that studies the essence, regularities, principles, methods, and forms of organizing the pedagogical process as a factor and means of human development throughout his or her life. While pedagogy studies the education and upbringing of a person, psychology examines the internal processes of the individual. Both subjects include separate branches of studying individuals at different stages of age development. Some of such branches are pedagogy and psychology of higher education.